Factors Affecting The Occurrence of Work Accidents on Garbage Collectors at Landfill in TTU District - Vebriana Heti Evisa Kasenube; Agus Setyobudi; Afrona E.L Takaeb (Lontar : Journal of Community Health, 2022)
Occupational health is one of the fields of public health that focuses on the working community both in the formal and informal sectors. Work accidents are health problems and harmful effects resulting from work; both accidents and diseases are caused by work. The purpose of this study was to description of factors affecting the occurrence of work accidents on garbage collectors at the landfill in TTU regency Tutop Bikomi Selatan district. The type of research used is descriptive research with a quantitative approach. The population of this study was all scavengers at TPAS Tutop, South Bikomi District, TTU Regency, with a total of 14 people. This is used as a sample in this investigation as well. The results showed that respondents had low education (85.7%), with 71.4% age group < 40 years, low knowledge level (71, 4%), lack of attitude (85.7%), not using PPE (64.3%), not available PPE (64.3%), availability of information (100%), lack of motivation (71.4%), supervision less (64.3%), had a work accident (92.9%). The accident was stabbed with a sharp object (85.7%) for the type of work. It is expected that waste scavenger workers should pay attention to the completeness of their time equipment to avoid complaints of diseases and other work hazards and be hastened to clean themselves if they feel disturbances in their body parts.